Level of androgens of pregnant women with psychoemotional state disorders stipulated by anxiety - Сюсюка, Володимир Григорович; Syusyuka, V. G. (Przemyśl: Nauka i studia, 2017)
Object of the research – assess the level of androgens of pregnant women with regard to their psychoemotional state. Group of examined women and methods of research. There were examined 86 pregnant women in ІІ and ІІІ trimester (28.2 ± 0.64 weeks). The main group comprises 60 pregnant women with medium and high level of state anxiety. The control group comprises 26 Pregnant women with anxiety level of 30 points and less, it stipulates the low level of state anxiety. For estimation of the state anxiety and trait anxiety the scale of Spielberger-Hanin was used.